Engineering laminated paper for SARS-CoV-2 medical gowns. (22nd April 2021) - Hossain, Laila; Maliha, Maisha; Barajas-Ledesma, Ruth; Kim, Jinhee; Putera, Kevin; Subedi, Dinesh; Tanner, Joanne; Barr, Jeremy J.; Banaszak Holl, Mark M.; Garnier, Gil
Abstract: The COVID-19 pandemic has highlighted the need for diversity in the market and alternative materials for personal protective equipment (PPE). Paper has high coatability for tunable barrier performance, and an agile production process, making it a potential substitute for polyolefin-derived PPE materials. Bleached and newsprint papers were laminated with polyethylene (PE) coatings of different thicknesses, and characterised for their potential use as medical gowns for healthcare workers and COVID-19 patients. Thicker PE lamination improved coating homogeneity and water vapour resistance. 49 GSM bleached paper with 16 GSM PE coating showed high tensile and seam strength, and low water vapour transmission rate (WVTR). Phi-X174 bacteriophage testing revealed that paper laminated with 15 GSM coating hinders virus penetration. This research demonstrates that PE laminated paper is a promising material for low cost viral protective gowns. Graphical abstract: Image 1 Highlights: Polyethylene (PE) laminated bleached paper was assessed as a medical gown material. High tensile and seam strength were achieved for the laminate composites. Viral penetration was hindered by a 49 GSM paper sheet with a 15 GSM PE coating. The laminated paper met medical gown material testing standards. Prototypes were praised by medical professionals when worn in a clinical setting.